Effect of a Plant Extract in Several Traits of Plymouth Rock Barred Hens and Pullets Challenged with Salmonella Typhimurium in a Rural Village in Central Mexico - García-López, J.C; Álvarez-Fuentes, G.; Pinos-Rodríguez, J.M; Jasso-Pineda, Y; Zapata-Pérez, E; Lee-Rangel, H.A; López-Aguire, S; Camacho-Escobar, M.A (Animal Review, 2016)
The effect of Chrysactinia mexicana Gray extract on poultry challenged with Salmonella typhimurium, was evaluated: 1) The aim of the survey was to understand the status quo of backyard poultry production in a rural area, 2). A field study with forty Plymouth Rock Barred Laying hens were used to test the effects of C. mexicana, and 3) 160 day old Plymouth Rock Barred pullets, were assigned to: T1 control; T2 control + S. typhimurium challenge; T3 control + S. typhimurium + C. mexicana; and T4 control + S. typhimurium + antibiotic. Crop, gizzard, proventriculus and duodenum colony forming units (CFU) were measured, and leukocyte and erythrocyte counts. In addition, weight gain and feed intake was measured. The liver, bursa, thymus and spleen were weighed. Results show that 75% of farmers in the community have hens. The main diseases in their fowl: respiratory 45%; diarrhea 35% and parasites 20%. 90% of farmers have no access to veterinary services. Results from the field study show differences (P<0.05) between the treated group with C. mexicana and the control group with no treatment. Feed intake, total weight gain and final body weight was higher (P<0.05) for control group among the other treatments. Treatment challenged plus antibiotic showed lower CFU counts than treatment with S. typhimurium and C. mexicana. Thymus, bursa and spleen weights were similar (P>0.05) for the C. mexicana and antibiotic treatments. Leukocyte and erythrocyte counts were lower (P<0.05) in control group. C. mexicana extract could be a tool to diminish bacteria in hens.